EVALUASI KETERSEDIAAN SARANA DAN PRASARANA USAHA KESEHATAN SEKOLAH PADA SMA SEDERAJAT SE-KECAMATAN PEUSANGAN KABUPATEN BIREUEN TAHUN AJARAN 2015/2016 - Zainuril Ikhsan; Amiruddin; Yeni Marlina; Razali (Lembaga Sepercenter, 2026)
School Health Facilities and Infrastructure are basic requirements for physical health activities in schools. Without adequate School Health Facilities and Infrastructure, it is difficult to expect school members to participate in physical health activities. The more School Health Facilities and Infrastructure available, the easier it is for school members to use and benefit from them. Conversely, the more limited the available UKS facilities and infrastructure, the more limited the opportunities for school members to use and utilise them in physical health activities. Thus, the availability of School Health Services facilities and infrastructure will affect the level and pattern of school members' participation in physical health activities. This study aims to determine the availability of UKS facilities and infrastructure in senior high schools in the Peusangan District of Bireuen Regency in the 2015/2016 academic year. This study is a descriptive qualitative study. The population in this study was all senior high schools in Peusangan District, Bireuen Regency, in the 2015/2016 academic year, which numbered eight schools. The researcher collected data using direct observation techniques at each school. Data processing in this study used the percentage method, starting from data collection, data analysis, review of research questions, and discussion of research results. From the data analysis, it was found that 67.30% of schools had UKS facilities and infrastructure that were in good condition, while 9.13% of all senior high schools in Peusangan District, Bireuen Regency, were in poor condition and unusable. The remaining 23.55% of the total UKS facilities and infrastructure needed as health facilities in schools were in the unavailable category.